2014
DOI: 10.1016/j.scitotenv.2014.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Management of irrigation frequency and nitrogen fertilization to mitigate GHG and NO emissions from drip-fertigated crops

Abstract: Drip irrigation combined with split application of fertilizer nitrogen (N) dissolved in the irrigation water (i.e. drip fertigation) is commonly considered best management practice for water and nutrient efficiency. As a consequence, its use is becoming widespread. Some of the main factors (water-filled pore space, NH4(+) and NO3(-)) regulating the emissions of greenhouse gases (i.e. N2O, CO2 and CH4) and NO from agroecosystems can easily be manipulated by drip fertigation without yield penalties. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 36 publications
7
54
2
2
Order By: Relevance
“…This is because drip irrigation reduces surface evaporation and deep percolation, obtaining high water use efficiency, while fertigation is wonderfully suitable for regulating the induction, time and level of fertilizer N application, thereby increasing N use efficiency (Darwish et al 2006). Some of these preference which are illustrate in literature (Asadi et al 2002;Lesschen et al 2011;Abalos et al 2014) through timely nitrogen utilization, excellent uniformity of N function, losses of environmental contamination, movement of tested N into the rooting zone by irrigation water and losses of soil compressed and mechanical deterioration to the plant. Furthermore, Papadopoulos (2000) reported that the fertigation of many plants under suppress irrigation is progressively expanding in several countries of the arid and semi-arid lands.…”
Section: Introductionmentioning
confidence: 98%
“…This is because drip irrigation reduces surface evaporation and deep percolation, obtaining high water use efficiency, while fertigation is wonderfully suitable for regulating the induction, time and level of fertilizer N application, thereby increasing N use efficiency (Darwish et al 2006). Some of these preference which are illustrate in literature (Asadi et al 2002;Lesschen et al 2011;Abalos et al 2014) through timely nitrogen utilization, excellent uniformity of N function, losses of environmental contamination, movement of tested N into the rooting zone by irrigation water and losses of soil compressed and mechanical deterioration to the plant. Furthermore, Papadopoulos (2000) reported that the fertigation of many plants under suppress irrigation is progressively expanding in several countries of the arid and semi-arid lands.…”
Section: Introductionmentioning
confidence: 98%
“…The observed nutrient distribution in fertigation is mainly due to the specific characteristics of the single ions, and soil hydraulic and chemical properties (i.e., CEC) [22]. Nevertheless, other factors can contribute to reducing or increasing ion mobility in the soil; for example, ion dynamics in the soil also depend on fertigation and irrigation frequency.…”
Section: Nutrients Applied By Fertigationmentioning
confidence: 99%
“…For the GWP assessment of FG a similar data set was used as for standard mineral fertilizers in combination with emission data of Abalos et al (2014), Kennedy et al (2013) and Scheer et al (2008), who measured GHG emissions in field experiments cropped with several horticultural plants (melons, tomatoes, wine and alfalfa) during various cultivation periods. On average, FG reduced N 2 O emissions leading to a lower N 2 O emission factor (0.8-0.9% N 2 O per kg N applied) for FG, which seems to be a better fit compared to the 1.25% given by the IPCC (2007).…”
Section: Stabilized Nitrogen Fertilizermentioning
confidence: 99%
“…Unfortunately, only very few field studies have been conducted focusing on CO 2 emissions due to fertigation. Abalos et al (2014) reported that the CO 2 emission during field cultivation with melon plants was enhanced by 9% for urea and 39% for calcium nitrate (CN). All emission data were additionally compared with ammonium nitrate (AN) in FG.…”
Section: Stabilized Nitrogen Fertilizermentioning
confidence: 99%